Chronotopographies: Chronotopes and the Crafting of Fictions - Silva e Silva, Fernando (UnderCurrents: Journal of Critical Environmental Studies, 2022)
In this paper, I delineate the workings of my concept of chronotopography. Starting from Bakhtin’s concept of chronotope—historico-poetic forms combining time, space and subjectivity—I define chronotopographical fiction as exploring radically other ways to combine and recombine the three elements of the chronotope. In the first section, I review some of the basic characteristics of the chronotope in Mikhail Bakhtin’s work. In the second section, I bring a definition of fiction in order to develop the concept of chronotopography as a unique kind of fiction that confronts existing chronotopes. I conclude that emphasizing the chronotopographical aspects of fiction can show us how to identify and compose new fictions that challenge hegemonic conceptions of time, space and subjectivity.